Anti-androgenic, anti-oestrogenic and antioxidant activities of aqueous extract of Laportea ovalifolia on adults rats. - Sylvain Nguedia Njina; Richard Simo Tagne; Bruno Phelix Telefo; Francois Ngoufack Zambou; Didiane Mefokou Yemele; Felicite Tchouanguep Mbiapo (International Journal of Phytomedicine, 2016)
Cancer is one of the most life-threatening diseases in which deregulating proliferation of abnormal cells invades and disrupts surrounding tissues. It constitutes seriouspublic health problems in both developed and developing countries. To evaluate the anti-androgenic, anti-estrogenic and antioxidant activities of Laportea ovalifolia (L. ovalifolia) in order to contribute to the search and the valorization of medicinal plants which could reduce mortality related to prostate cancer. The evaluation of the anti-androgenic activity were carried out on castrated male rats receiving simultaneous daily administration of testosterone and different doses of aqueous extract of L. Ovalifolia during a period of 10 days. That of the anti-estrogenic activity was carried out on mature ovariectomized female rats receiving for a week simultaneous daily administration of estradiol and different doses of plant extract. The evaluation of the in vivo antioxidant activity of L. Ovalifolia aqueous extract was carried on adult male rats receiving simultaneous daily administration of naphthalene and different doses of extract, for 15 days. For its in vitro antioxidant activity, the amounts of phenolic compounds in plant extracts were determined as well as the total flavonoid contents of the crude extracts. Also, the DPPH scavenging activity of the plant extract was determined as well as its reducing power. As compare to the 0 mg/kg testosterone primed castrated rat, those treated with the various dose of the plant extract presented either a significant decrease in weights of all their reproductive tissues (P˂0.01 - P˂0.001) or a significant increase (P˂0.001) in their serum level of testosterone. For all the plant extract treated ovariectomized rats, similar trends were observed for the relative uteri weight (P˂0.01) and that of the serum level of estradiol (P˂0.001). Plant extract contains 13.33±0.1 mg GAE/g and 05.27±0.17 mg CATE/g of phenolic and flavonoids compounds respectively and exhibits DPPH radical scavenging ability as well as ferric-reducing antioxidant power. Relatively to animals treated at 0 mg/kg, the various doses of the plant extract significantly increased (P˂0.05 - P˂0.001) the activity of catalase (in liver, lungs and the serum), SOD (in liver and heart) and peroxidase (in liver, heart, serum and lungs). It also significantly reduces (P˂0.001) the level of nitric oxide in the liver, heart, lungs, kidneys and serum. Globally, these results denote the anti-androgenic, anti-estrogenic and antioxidant potential of L. ovalifolia.